Neuroblastoma arginase activity creates an immunosuppressive microenvironment that impairs autologous and engineered immunity - Mussai, Francis; Egan, Sharon A.; Hunter, Stuart; Webber, Hannah; Fisher, Jonathan; Wheat, Rachel; McConville, Carmel; Sbirkov, Yordan; Wheeler, Kate; Bendle, Gavin; Petrie, Kevin; Anderson, John; et al. (American Association for Cancer Research, 2015)
Neuroblastoma is the most common extra cranial solid tumour of childhood, and survival remains poor for patients with advanced disease. Novel immune therapies are currently in development, but clinical outcomes have not matched preclinical results. Here, we describe key mechanisms in which neuroblastoma inhibits the immune response. We show that murine and human neuroblastoma tumour cells suppress T cell proliferation, through increased arginase activity. Arginase II is the predominant isoform expressed and creates an arginine deplete local and systemic microenvironment. Neuroblastoma arginase activity results in inhibition of myeloid cell activation and suppression of bone marrow CD34+ progenitor proliferation. Finally we demonstrate that the arginase activity of neuroblastoma impairs NY-ESO-1 specific TCR and GD2-specific CAR engineered T cell proliferation and cytotoxicity. High arginase II expression correlates with poor survival for neuroblastoma patients. The results support the hypothesis that neuroblastoma creates an arginase-dependent immunosuppressive microenvironment in both the tumour and blood that leads to impaired immune surveillance and sub-optimal efficacy of immunotherapeutic approaches.